Surface engineering to manipulate solar energy for thermal management - Fei, Jipeng (Nanyang Technological University, 2023)
The use of sustainable energy sources has risen significantly in recent years due to the tremendous pollution and waste associated with traditional fossil fuels, and the urgent needs of decarbonization. Specifically, solar energy is one of the most important infinite energy resources since it is constantly available to earth in abundance. This not only enables living organisms to thrive, but also can be used by industry. Surfaces receiving solar energy are major energy-conversion sites. In other words, surface property determines the utilization of sunlight in various applications. Typically, a designed surface could be solar absorptive, transmissive, or reflective, offering possibilities for thermal management. More specifically, surfaces with rational structural and material design could exhibit various functions including switchable/tunable optical property, thermal properties, and photothermal properties. It is clear that surface engineering provides abundant opportunities to utilize or manage the infinite solar energy in energy-saving applications. To clearly demonstrate the effectiveness of surface property in solar energy utilization/ management, two novel technologies (solar steam generation and passive cooling) are investigated in this thesis. Firstly, solar steam generation requires an efficient photothermal generator (surficial membrane) with an effective porous structure. Herein, we functionalized Ti3C2 MXene material as a broadband and high efficiency photothermal converter, which combines with a stable hierarchical porous organic membrane to realize ~50 ℃ surface temperature, 92.1% solar-to-steam efficiency under 1 Sun illumination, and 97.5% salt rejection rate, leading to efficient water harvesting/purification/desalination. The main contribution of this work is the systematic design of 2D solar steam generator, where photothermal efficiency, water transportation and thermal management are optimized within the same setup, which results in ultrahigh evaporation rate and solar to steam efficiency towards the theoretical limitation. Following this, we coupled surface electrostatic field as a generic idea to further enhance solar energy utilization efficiency (faster steam generation rate). It was proven that under electrostatic field, water evaporation rate was enhanced up to 15.6% compared to a normal steam generator under the same sunlight illumination, due to weakened hydrogen bonding networks, smaller water clusters as revealed by in-situ Raman spectroscopy. The main contribution and finding of this work are an effective enthalpy reduction method through applying an external field that could be universally applied to different solar steam generators. Besides, the mechanism of electrostatic influence on water molecule network has been investigated, which inspired rational manipulation of water structure to tune evaporative behavior. It is worth noting that efficacy of electrostatic field is negatively correlated to temperature (depending on solar intensity), providing the possibility for thermal management (currently under investigation and proposed in future work section). Inspired by a color difference of designed solar steam generator after water saturation, we found that hierarchical porous structure exhibits contrasting optical property under various wetting conditions. Based on this finding, we developed a coating layer with switchable optical properties for solar energy management. In this work, we theoretically confirmed a minimized scattering efficiency introduced by reduced refraction index difference at material boundaries. Moreover, a surface structure containing vertically aligned micro-size pores within a nano-porous matrix was developed by applying an optimized one-step phase change method. Through matching the refractive index between porous membrane and filling liquids, Mie scattering along pore boundaries was successfully tuned, achieving the switch between solar transmissive and reflective modes. Furthermore, we demonstrated significant thermal management by applying a designed coating with both radiative cooling and solar heating functions. The main contribution of this work is verification of the effective liquid matching method for optical regulation, which pushed the optical contrast to an extreme value that could facilitate both optical and thermal management. However, we found that the radiative cooling capability of the designed hierarchical porous membrane is not as obvious as reported by researchers from other countries (Mainly US and China). Thus, we theoretically investigated the radiative cooling criteria in Singapore, complemented by experimental verification. In fact, Singapore exhibits typical tropical climate with high temperature all year round, where its relative humidity and solar intensity are significantly higher than those of most other regions in the world. It was found that high relative humidity (averagely ~65% at sunny daytime and higher on cloudy days) leads to an apparently narrowed atmospheric window, which strongly hinders the long-wavelength infrared (LWIR) radiation. Meanwhile, daytime solar intensity in Singapore can reach more than 1200 W/m2, which is much higher than that in other regions. The much higher solar energy leads to further compensation of radiative cooling power, making sub-ambient cooling very challenging to achieve. It was found that solar reflection works as the dominant factor in typical tropical climate to reach a daytime sub-ambient cooling, while LWIR emission contribution is much less significant than that in the mid-latitude area. Since thermal radiation works poorly under tropical climates, other surface passive cooling strategies need to be adopted to enhance cooling performance. Thus, we introduced another conventional passive cooling technique, i.e., evaporation cooling by water vaporization. Accordingly, an optically modified, high water content hydrogel matrix was designed as a passive radiative cooler at daytime, which is called metagel. The metagel radiative cooler utilizes both radiative and evaporative cooling processes within an individual composite, while also exhibiting strong visible-NIR (near infrared) Mie scattering minimizes the incident solar energy, keeping surface temperature low. Experimentally, it exhibits up to 10 times higher cooling power than conventional radiative coolers under the tropical climate, resulting in up to 6 ℃ sub-ambient cooling performance at daytime. Different from conventional radiative coolers, the metagel transfers part of the incident solar energy to the internal energy of the water vapor released. This approach effectively reduces the net solar energy absorbed, providing a new strategy to design low reflectance sub-ambient passive cooler. Low-reflectance is necessary in certain applications such as building coating, where too high reflectance may cause light pollution. This work directly shows that surface material and structural design enables an integration of different passive cooling approaches, rationally inhibiting absorption of incident solar energy, realizing effective surface thermal management. The main contribution of this work is the proof-of-concept that shows multiple passive cooling strategies could be integrated into a single composite with rational optofluidic design, where the cooling performance can be greatly enhanced.